The Importance of Place in Advancing Sustainable Mobility Thinking and Practice - Caulfield, Brian (My University, 2026)
How, why and where people move, and the larger processes that impact these decisions, are key concerns within the discipline of geography. Yet even though substantial research on mobility has been undertaken, particularly in recent years through the ‘mobilities turn’, limited attention has been paid in geography or mobility studies to mobility's place-based aspects. We argue that including the concept of place is critical to advance sustainable mobility. Unlocking more sustainable forms of mobility is a necessary part of climate action, progressing climate goals, and enhancing liveability and human wellbeing. To date, many sustainable mobility policies have mostly been top-down, responding to international or national imperatives and focussed on critical infrastructure development and active travel. Very often they are presented as ‘one size fits all’ solutions that fail to account for local, place-based and social differences impacting on uptake and social acceptability. We argue that mobility needs to be better understood through the lens of the lived experience as an embodied, differentiated and political process. Further, a place-based approach to sustainable mobility is required to achieve meaningful behavioural change and more explicit attention needs to be focussed on the intersection of place and mobility. For transformative policy shifts at national and other scales to have real-world impact, they must be informed by the local context. The research reviewed here supports our argument that for sustainable mobility to succeed, more attention needs to be paid to place, and the everyday aspects of movement. A place-based approach to sustainable mobility should be locally grounded, place specific, and take into account place characteristics and capabilities. We argue that for sustainable mobility policies to enable impactful change, place must be central to thinking, planning and practice.
PUBLISHED
Keywords: Smart & Sustainable Planet; Environmental aspects of transportation; Transport